2019
DOI: 10.14814/phy2.14213
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium excretion predict increased depression in urban adolescents

Abstract: This study examined the prospective role of urinary sodium and potassium excretion in depressive symptoms among urban, low‐income adolescents, and whether these relationships vary by gender. A total of 84 urban adolescents (mean age 13.36 years; 50% male; 95% African American) self‐reported on their depressive symptoms at baseline and 1.5 years later. At baseline, the youth also completed a 12‐h (overnight) urine collection at home which was used to measure sodium and potassium excretion. After adjusting for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…Previous evidence showed that the prevalence of depressive symptoms was higher among urban adolescents [ 45 ]. Mrug et al found that increased sodium overnight excretion and reduced potassium excretion rates could predict more severe depressive symptoms occurring 1.5 years later in urban areas among African American adolescents [ 46 ]. Furthermore, a lack of family cohesion may lead to comorbid depressive and anxiety symptoms among adolescents in China [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence showed that the prevalence of depressive symptoms was higher among urban adolescents [ 45 ]. Mrug et al found that increased sodium overnight excretion and reduced potassium excretion rates could predict more severe depressive symptoms occurring 1.5 years later in urban areas among African American adolescents [ 46 ]. Furthermore, a lack of family cohesion may lead to comorbid depressive and anxiety symptoms among adolescents in China [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of their influence on mental health is still unknown, while a number of possible factors that may contribute to the positive impact are indicated [18]. Among them, there are specific nutrients, which are known as such that may be related to mental health and for which fruit and vegetables are indicated as a valuable sources in diet, such as complex carbohydrates [20] and fiber [21], being associated with glycemic index [22], C vitamin [23], B vitamins [24], carotenoids [25], potassium [26], and polyphenols [27]. The other explanations are associated with either possibility of reverse mechanism (higher level of mental health may promote better diet, including higher fruit and vegetables intake) [28], or psychological explanation (following better diet, including higher fruit and vegetables intake may promote more positive emotions and better mental health) [29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, people who consume foods that are high in sodium and low in potassium are more likely to develop symptoms of depression. [39] Furthermore, a lack of amino acids and zinc in the diet may cause depression because of enhanced levels of serotonin and dopamine in the body. [38] These ndings suggest that countries should reconsider their existing policies and initiate programs for promoting healthy dietary habits among adolescents.…”
Section: Discussionmentioning
confidence: 99%